Serum microRNA-4297 is a sex-specific predictive biomarker of glioma grade and prognosis - Xu, Wenshen; Huang, Liming; Xie, Bingsen; Yang, Bin (Frontiers in Neurology, 2022)
Background Gliomas account for nearly 80% of brain cancers, tending to occur more frequently in men with adverse outcomes. Emerging microRNAs have been positioned as promising predictors for glioma's histological grade and prognosis. However, there have been few studies concerning the sex-biased impacts on the clinical approach for the potential microRNA-4297 (miR-4297). Methods We utilized GSE139031micro-RNAs profiling to analyze serum miR-4297 expression in glioma. A total of 114 newly diagnosed glioma patients at the First Affiliated Hospital of Fujian Medical University from January 2017 to February 2021 were recruited and prospectively followed up. The association of miR-4297 levels with glioma grade and prognosis was investigated. Luciferase reporter gene assays and genotype analyses were carried out to explore the potential mechanism of sexually dimorphic miR-4297 in glioma. Results Serum miR-4297 levels were notably down-regulated in glioma. Besides, serum miR-4297 levels were positively associated with the high grades, which were exclusively present for females. The positive correlations of miR-4297 with O6-methylguanine-DNA methyltransferase (MGMT) protein and mean platelet volume were also observed in females. IDH-mutant females had decreased miR-4297. Median PFS time for females with miR-4297 ≥ 1.392 was distinctly shorter than those with miR-4297 <1.392 (12.3 months vs. 42.89 months, p = 0.0289). Based on multivariate logistic regression, miR-4297-based equation model was established as FHGRS. AU-ROC analysis revealed FHGRS exhibited a robust performance in predicting high-grade glioma in females (p < 0.001), whereas there was no such relationship in males. Furthermore, the MGMT-3'UTR variant rs7896488 in the specific binding region of miR-4297 was correlated with prognosis. Conclusion Our study uncovers sex-dependent characterization of serum miR-4297 in predicting glioma grade and the relapse risk for female patients, which underscores the clinical benefits of sex-specific analysis in non-coding RNA research.